Adaptation memory in photoreceptors: different mechanisms in rods and cones - Nikolaeva, Darya A.; Nekrasova, Maria A.; Rotov, Alexander Yu.; Astakhova, Luba A. (Frontiers in Molecular Neuroscience, 2023)
Vertebrate rods and cones operate over a wide range of ambient illumination, which is provided by light adaptation mechanisms regulating the sensitivity and speed of the phototransduction cascade. Three calcium-sensitive feedback loops are well established in both rods and cones: acceleration of the quenching of a light-activated visual pigment and cGMP synthesis by guanylate cyclase, and increased affinity of ion channels for cGMP. Accumulating evidence suggests that the molecular mechanisms of light adaptation are more complex. While investigating these putative mechanisms, we discovered a novel phenomenon, observing that the recovery of light sensitivity in rods after turning off non-saturating adaptive light can take tens of seconds. Moreover, after a formal return of the membrane current to the dark level, cell sensitivity to the stimuli remains decreased for a further 1–2 min. We termed this phenomenon of prolonged photoreceptor desensitization ‘adaptation memory’ (of previous illumination) and the current study is focused on its detailed investigation in rods and an attempt to find the same phenomenon in cones. In rods, we have explored the dependencies of this phenomenon on adapting conditions, specifically, the intensity and duration of adapting illumination. Additionally, we report that fish and frog red-sensitive cones possess similar features of adaptation memory, such as a drop in sensitivity just after the steps of bright light and slow sensitivity recovery. However, we have found that the rate of this process and its nature are not the same as in rods. Our results indicate that the nature of the temporary drop in the sensitivity in rods and cones after adapting steps of light is different. In the rods, adaptation memory could be attributed to the existence of long-lasting modifications of the components of the phototransduction cascade after adapting illumination. In cones, the observed form of the adaptation memory seems to be due to the sensitivity drop caused by a decrease in the availability of the visual pigment, that is, by bleaching.